DETERMINAN PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA: ANALISIS PEMBIAYAAN BERMASALAH, KECUKUPAN MODAL, LIKUIDITAS PEMBIAYAAN, DAN EFISIENSI OPERASIONAL TAHUN 2017–2024 - Adinda Maulana Diningrat; Zainal Arifin (Journal of Financial Economics & Investment, 2026)
Islamic banking in Indonesia faces a structural paradox as the large muslim demograpic potential has yet to translate into a significant market share. This study aims to analyze the determinants of profitability among 8 Indonesia Islamic Commercial Banks over the period 2017-2024, employing a quantitative approach through panel data regression. Return on Assets serves as the dependent variabel representing profitability, while the independent variables comprise Non-Performig Financing, Capital Adequancy Ratio, Financing to Deposit Ratio, and the Operational Effeciency Ratio. The research sample was determined through purposive sampling, selecting banks with complete data availability throughout the observation period. Model selection procedures indicate that the Common Effect Model is the mos appropriate specification for this study. Simultaneously, all independent variables exert a significant influence on profitability. Partially, operational efficiency emerges as the most dominant determinant, exerting a significant negative effect on profitability, followed by non-performing financing and capital adequancy ratio, both of which also negatively and significanly affect profitability. Conversely, the financing-to-deposit ratio yield no significant effect. These findings suggest that structural operational inefficiency constitutes the primary obstacle to improving the provitability and competitiveness of Indonesia’s Islamic banking industry.